Handbook of smart coatings for materials protection - Makhlouf, Abdel Salam Hamdy (Woodhead Publishing series in metals and surface engineering ;, 2014)
This book reviews the new generation of smart coatings for corrosion and other types of material protection. It explores the fundamentals of smart coatings for materials protection including types, materials, design, and processing as well as includes a focus on smart coatings with self-healing properties for corrosion protection. This is a valuable reference for those concerned with preventing corrosion, particularly of metals, professionals working within the surface coating industries, as well as all those with an academic research interest in the field. --